THE ROLE OF THE CONCEPT OF ‘CHINA’S PEACEFUL RISE IN CHINA'S FOREIGN POLICY: EVOLUTION AND IMPACT (1993-2013) (Вісник: Міжнародні відносини, 2025)
Abstract. This article analyses the evolution of the foreign policy of the People's Republic of China (PRC) in the late 20th and early 21st centuries, focusing on the concept of ‘peaceful rise’ (later ‘peaceful development’) as a key element of China's foreign policy strategy during this period. The study covers the reigns of Jiang Zemin (1993-2003) and Hu Jintao (2003-2013), analysing their foreign policy initiatives, economic reforms and influence on the geopolitical positioning of the PRC. The article examines key aspects of the concept of ‘peaceful rise,’ the subsequent transition to the concept of ‘peaceful development,’ and assesses the concept's impact on the formation of China's foreign policy strategies, its main theoretical foundations, and practical implications for China's global integration.
Keywords: peaceful rise; geopolitical positioning; “one country, two systems”; peaceful development; diplomatic interaction